Gainesville's Urban Forest Structure and Composition - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS)
FOR-214, a 3-page illustrated fact sheet by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, provides an overview of the composition and structure of the urban forest found in Gainesville, Florida. Includes references. Published by the UF School of Forest Resources and Conservation, April 2009.